2019
DOI: 10.3390/su11082271
|View full text |Cite
|
Sign up to set email alerts
|

Double-Edged Effects of Socially Responsible Human Resource Management on Employee Task Performance and Organizational Citizenship Behavior: Mediating by Role Ambiguity and Moderating by Prosocial Motivation

Abstract: Previous literature has explored the positive effects of socially responsible human resource management (SRHRM) on employees, leaving potential dark sides largely ignored. By integrating situational-strength theory and motivation literature, this study investigates the double-edged effects of SRHRM on employee performance. Based on a sample of 314 employee–supervisor dyads from three companies, we found that SRHRM could increase employees’ organizational citizenship behavior (OCB) while decreasing their task p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 72 publications
2
27
0
2
Order By: Relevance
“…Education is important too, but when the relationship to the work done is missing, it becomes secondary. In this context, Shao et al [73] highlighted the need for socially responsible human resource management, whose application, inter alia, gradually transforms employee responsibility awareness into organizational competitiveness and sustainable development.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Education is important too, but when the relationship to the work done is missing, it becomes secondary. In this context, Shao et al [73] highlighted the need for socially responsible human resource management, whose application, inter alia, gradually transforms employee responsibility awareness into organizational competitiveness and sustainable development.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Shao et al [83] concluded that perceived SR-HRM increases employees' organisational citizenship behaviour, although not task performance, through affective and cognitive mechanisms. In addition, Shao et al [84] studied the effects of SR-HRM on employee performance, adding the moderator effect of prosocial motivation. López-Fernández et al [23] found a link between SR-HRM and employee commitment, and that the employees' perceptions affect this relationship.…”
Section: Sub-period 2017-2019mentioning
confidence: 99%
“…al. (2019) (Shao, 2019). Penelitian terdahulu mengungkapkan bahwa karyawan yang ada di sebuah perusahaan dapat memiliki pandangan yang beragam mengenai kegiatan CSR yang dimiliki perusahaan yang secara umum dipengaruhi oleh karakter dari masingmasing individu serta lingkungan kerja karyawan tersebut (Rodrigo & Arenas, 2008).…”
Section: Pendahuluanunclassified
“…Oleh sebab itu praktek HRM merupakan faktor yang penting dalam membentuk sebuah organizational climate yang baik (Mossholder et. al., 2011) karena karyawan sebuah perusahaan akan melihat ciri-ciri lingkungan kerja mereka dengan cara melihat hal-hal yang diterima dan dianggap baik oleh perusahaan serta konsekuensi yang kemungkinan ditanggung akibat perilaku tertentu sehingga para karyawan akan menyesuaikan perilaku mereka sesuai dengan pemahaman tersebut (Burke et.al., 1992, dalam Shen & Zhang, 2017 (Shao, et. al., 2019…”
Section: Hubungan Antara Srhrm Dengan Employee Support For Csrunclassified